The Inclusion of Third Parties (Joinder) in Multi-Party International Arbitration Cases: The Perspective of Indonesian Arbitration - King William; Gatot P. Soemartono (Jurnal Daulat Hukum, 2025)
Indonesia also officially recognizes international arbitration, which is articulated in Article 1 paragraph (9) of the Arbitration Law, as amended following Constitutional Court Decision No. 100/PUU-XXII/2024. This provision states: "International Arbitral Award is an award rendered by an arbitral institution or a sole arbitrator outside the legal jurisdiction of the Republic of Indonesia, or an award by an arbitral institution or a sole arbitrator which, pursuant to the provisions of the law of the Republic of Indonesia, is deemed to be an International Arbitral Award” (Putusan MK No. 100/PUU-XXII/2024, 2024). The joinder of third parties presents a key challenge in international arbitration due to its conflict with the fundamental principle of party consent. This article examines joinder's application in Indonesian arbitration, specifically analyzing the principles of consent and public order. This research used a normative legal research method, the study analyzes relevant regulations to determine joinder's legality. The findings conclude that the joinder principle is implicitly acknowledged and enforceable in Indonesian arbitration. The article offers an understanding of its implementation and provides recommendations for regulators to ensure legal certainty in Indonesia.